PENDAMPINGAN KADER DALAM PENGOLAHAN DAN PEMBERIAN MAKANAN PENDAMPING ASI BERBASIS KEARIFAN LOKAL DI DESA PONDOK MEJA, KABUPATEN MUARO JAMBI, PROVINSI JAMBI - Asparian Asparian; Silvia Mawarti Perdana; Lia Nurdini (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2020)
Children under two years is a golden period of growth and development that determines the quality of health at later age. One of the nutritional factors, in addition to breast milk, which determines the nutritional status of under-two children is complementary feeding with the principles of nutritious and safety, it must also be available locally and affordable prices. This community service activity aims to increase the knowledge, attitudes and skills of cadres in processing and providing complementary feeding to children. This activities include: focus group discussions related to malnutrition problems, causes and solutions by involving puskesmas, PKK, and village government; and training on processing and providing complementary feeding based on local wisdom to cadres. The results of this community service activity showed that there wassignificant differences in the cadres’s knowledge in processing and providing complementary feeding compared to before training activity (test scores from 67.59 to 75.38). Cadre training in processing and providing complementary feeding needs to be carried out sustainably as an effort to improve the nutritional status of under-two children.